Effects of T2DM on cancer progression: pivotal precipitating factors and underlying mechanisms - Zhang, Yu-Yuan; Li, Yong-Jiang; Xue, Chun-Dong; Li, Shen; Gao, Zheng-Nan; Qin, Kai-Rong (Frontiers in Endocrinology, 2024)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder affecting people worldwide. It is characterized by several key features, including hyperinsulinemia, hyperglycemia, hyperlipidemia, and dysbiosis. Epidemiologic studies have shown that T2DM is closely associated with the development and progression of cancer. T2DM-related hyperinsulinemia, hyperglycemia, and hyperlipidemia contribute to cancer progression through complex signaling pathways. These factors increase drug resistance, apoptosis resistance, and the migration, invasion, and proliferation of cancer cells. Here, we will focus on the role of hyperinsulinemia, hyperglycemia, and hyperlipidemia associated with T2DM in cancer development. Additionally, we will elucidate the potential molecular mechanisms underlying their effects on cancer progression. We aim to identify potential therapeutic targets for T2DM-related malignancies and explore relevant directions for future investigation.